AN INDIVIDUAL APPROACH HAS AN IMPORTANT PEDAGOGICAL VALUE IN ALL STAGES OF EDUCATION (British Journal of Global Ecology and Sustainable Development, 2025)
The article analyzes the social orientation of individual education in the formation of modern student personality, its component, personality-oriented technological factors, the compatibility of the combination of pedagogical approach that ensures the harmony of purpose and content, the importance of individual approach in all stages of the educational process.